Fostering Tolerance through Technology: Digital Transformation of Islamic Religious Education in Bengkulu’s Public High Schools - Satrisno, Hengki; Septiria, Dalima; Irawan, Bambang; Onia, Saifaldin Idris; Rulitawati (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to: (1) identify the forms and types of digital media used in the teaching of Islamic Religious Education (IRE) in public senior high schools in Bengkulu Province; (2) analyze strategies for integrating the values of religious moderation into digital-based content; and (3) describe the benefits and challenges encountered in implementing digitalized learning with a focus on strengthening the values of religious moderation. This descriptive qualitative research employed purposive sampling to select informants, which included teachers, school principals, vice principals for curriculum, and 11th and 12th-grade students who actively participated in online or hybrid IRE learning. Data were collected through observation, interviews, and documentation. Data validity was ensured through triangulation of sources and methods. Data analysis involved data reduction, display, and conclusion drawing/verification. The substantial benefits of digital applications for humans in the modern era position media as a tool with various advantages, particularly in terms of better accessibility, interactive content delivery, diverse learning resources, improved communication and collaboration, and support for autonomous and personalized learning. Efforts to integrate digital media into IRE learning include the use of online learning platforms, educational videos, collaborative projects, blogs or online journals, social media, online discussion forums, multicultural content, live streaming, and webinars. The values of religious moderation that must be incorporated into Islamic Religious Education encompass attitudes and behaviors that are balanced, open-minded, and respectful of religious diversity in practice.